The cladistic analysis of serine/threonine protein kinase KIN10 and peculiarities of its an expression in different organs of Arabidopsis thaliana - Krasnoperova, E. E.; Isayenkov, S. V.; Karpov, P. A.; Yemets, A. I.; Blume, Ya. B. (Reports of the National Academy of Sciences of Ukraine, 2016)
The cladistic analysis and the phylogenetic tree construction of the closest homologs of protein kinase KIN10 are performed. The obtained results have shown the membership of KIN10 and its two closest homologs in plants (KIN11 (P92958) and Akin11 (Q9FLZ3)) to the unique subfamily of protein kinases SnRK1. In addition, the expression level of KIN10 gene in different plant organs are characterized. The highest level of KIN10 transcripts is observed in the green photosynthetic part of the plant, where KIN10 protein kinase regulates the biosynthetic and signaling processes.